Comparative Study of the Concept of Human Creation in Qs. Al-Mu’minun Verses 12–14 Perspective of Hamka and Wahbah Zuhaili - Anggi Mahendra; Ainur Rhain; Kharis Nugroho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the interpretation of Quranic embryology in Surah Al-Mu'minun, verses 12–14, according to Hamka in Tafsir al-Azhar and Wahbah Zuhaili in Tafsir al-Munir, and to identify similarities and differences in their interpretive methodologies. This study uses a qualitative approach with library research and a comparative interpretation method (tafsir muqaran). Primary data were obtained from the interpretation of Surah Al-Mu'minun, verses 12–14 in both tafsir books, while secondary data came from literature related to scientific interpretation, Quranic embryology, and contemporary interpretation methodology. Data collection was conducted through documentation and analyzed using content analysis. The results of this study indicate that Hamka and Wahbah Zuhaili both interpret the stages of human creation, from conception to conception, nufah, 'alaqah, mudghah, bone formation, wrapping with flesh, and the breathing of the soul, as evidence of God's power. However, Hamka emphasizes a narrative, reflective, and social approach by linking the verses to the development of science and human values. In contrast, Wahbah Zuhaili uses a systematic, linguistic, and theological approach with an emphasis on the aspects of monotheism and human resurrection. This study concludes that the differences in interpretation are influenced by the intellectual background and methodology of each exegete. This research contributes to the development of scientific and comparative interpretations in contemporary Qur'anic studies.